Effect of Adjunctive Simvastatin on Depressive Symptoms Among Adults With Treatment-Resistant Depression: A Randomized Clinical Trial - Husain, M. Ishrat; Chaudhry, Imran B.; Khoso, Ameer B.; Kiran, Tayyeba; Khan, Nawaz; Ahmad, Farooq; Hodsoll, John; Husain, M. Omair; Naqvi, Haider A.; Nizami, Asad T.; Chaudhry, Nasim; Khan, Hazrat A.; et al. (JAMA network open, 2023)
Immune-metabolic disturbances have been implicated in the pathophysiology of major depressive disorder and may be more prominent in individuals with treatment-resistant depression (TRD). Preliminary trials suggest that lipid-lowering agents, including statins, may be useful adjunctive treatments for major depressive disorder. However, no adequately powered clinical trials have assessed the antidepressant efficacy of these agents in TRD. To assess the efficacy and tolerability of adjunctive simvastatin compared with placebo for reduction of depressive symptoms in TRD. This 12-week, double-blind, placebo-controlled randomized clinical trial was conducted in 5 centers in Pakistan. The study involved adults (aged 18-75 years) with a Diagnostic and Statistical Manual of Mental Disorders (Fifth Edition) major depressive episode that had failed to respond to at least 2 adequate trials of antidepressants. Participants were enrolled between March 1, 2019, and February 28, 2021; statistical analysis was performed from February 1 to June 15, 2022, using mixed models. Participants were randomized to receive standard care plus 20 mg/d of simvastatin or placebo. The primary outcome was the difference between the 2 groups in change in Montgomery-Åsberg Depression Rating Scale total scores at week 12. Secondary outcomes included changes in scores on the 24-item Hamilton Rating Scale for Depression, the Clinical Global Impression scale, and the 7-item Generalized Anxiety Disorder scale and change in body mass index from baseline to week 12. C-reactive protein and plasma lipids were measured at baseline and week 12. A total of 150 participants were randomized to simvastatin (n = 77; median [IQR] age, 40 [30-45] years; 43 [56%] female) or placebo (n = 73; median [IQR] age, 35 [31-41] years; 40 [55%] female). A significant baseline to end point reduction in Montgomery-Åsberg Depression Rating Scale total score was observed in both groups and did not differ significantly between groups (estimated mean difference for simvastatin vs placebo, -0.61; 95% CI, -3.69 to 2.46; P = .70). Similarly, there were no significant group differences in any of the secondary outcomes or evidence for differences in adverse effects between groups. A planned secondary analysis indicated that changes in plasma C-reactive protein and lipids from baseline to end point did not mediate response to simvastatin. In this randomized clinical trial, simvastatin provided no additional therapeutic benefit for depressive symptoms in TRD compared with standard care. ClinicalTrials.gov Identifier: NCT03435744.